Effect of alteplase on the CT hyperdense artery sign and outcome after ischemic stroke. (12th January 2016) - Mair, Grant; von Kummer, Rüdiger; Morris, Zoe; von Heijne, Anders; Bradey, Nick; Cala, Lesley; Peeters, André; Farrall, Andrew J.; Adami, Alessandro; Potter, Gillian; Cohen, Geoff; Sandercock, Peter A.G.; et al.
Abstract : Objective: To investigate whether the location and extent of the CT hyperdense artery sign (HAS) at presentation affects response to IV alteplase in the randomized controlled Third International Stroke Trial (IST-3). Methods: All prerandomization and follow-up (24–48 hours) CT brain scans in IST-3 were assessed for HAS presence, location, and extent by masked raters. We assessed whether HAS grew, persisted, shrank, or disappeared at follow-up, the association with 6-month functional outcome, and effect of alteplase. IST-3 is registered (ISRCTN25765518). Results: HAS presence (vs absence) independently predicted poor 6-month outcome (increased Oxford Handicap Scale [OHS]) on adjusted ordinal regression analysis (odds ratio [OR] 0.66, p < 0.001). Outcome was worse in patients with more (vs less) extensive HAS (OR 0.61, p = 0.027) but not in proximal (vs distal) HAS ( p = 0.420). Increasing age was associated with more HAS growth at follow-up (OR 1.01, p = 0.013). Treatment with alteplase increased HAS shrinkage/disappearance at follow-up (OR 0.77, p = 0.006). There was no significant difference in HAS shrinkage with alteplase in proximal (vs distal) or more (vs less) extensive HAS ( p = 0.516 and p = 0.580, respectively). There was no interaction between presence vs absence of HAS and benefit of alteplase on 6-month OHS ( p = 0.167). Conclusions: IV alteplase promotes measurable reduction in HAS regardless of HAS location or extent. Alteplase increased independence at 6 months in patients with and without HAS. Classification of evidence: This study provides Class I evidence that for patients within 6 hours of ischemic stroke with a CT hyperdense artery sign, IV alteplase reduced intra-arterial hyperdense thrombus.